Universal internet of things system powered by FIWARE - Lopes, Diogo Alexandre Rodrigues (2018)
Internet of Things has grown exponentially in recent years and will continue to grow for some time, with more and more IoT devices available in the consumer market and specific, there are also increasingly systems and platforms that use and support these devices, thus providing the possibility to view information by these collected or control them through a graphical interface, which can be a website or an application. Due to the expansion of the Internet market of Things resulting from a wide variety of devices and systems from different manufacturers it is difficult to find systems that are compatible with all or several devices from different manufacturers, since many use proprietary communication protocols. This dissertation aims at the development of an universal IoT system using the FIWARE Platform, promoted by the European Commission, which allows the use of the modular components that make up this platform to develop the intended universal system. A set of microcontrollers coupled to various sensors and actuators will be used to test the system and to verify the proper functioning of the same and each FIWARE component used, which will communicate with the system transmitting the collected data or receiving commands in the case of the actuators. These "things" were used in the context of a fictional use case simulating a real implementation of the system, having been able to function properly, able to receive data from the sensors, present data when necessary, and control the actuators.